THE EFFECT OF SUNLIGHT AND HPLN MERCURY FLUORESCENT LAMP ON PHOTODEGRADATION OF RIBOFLAVIN IN AQUEOUS SOLUTIONS - Nida Ghani; Adeel Arsalan; Mirza Tasawer Baig; Kiran Qadeer; Hina Abrar; Hina Yasin; Kaneez Fatima; Maria Ashfaq (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
The study is conducted to evaluate the effect of sunlight (SL) and mercury HPLN fluorescent lamp (ML) on riboflavin (RF) aqueous solution containing. The pure solutions of RF (5 x 10-5 M) were exposed to SL and ML for 20 min. The pure solutions of RF possessed more photodegradation, in presence of SL as compared to ML. Moreover, the photolysis of pure solutions of RF possessed first-order rate constant. The values of first-order rate constant (kobs) of RF irradiated in SL and ML were obtained, 2.503×10−2 min−1 and 8.545×10-3 min-1, respectively, from slope of the plot of log concentration of RF against time at pH 7.4. The shelf-lives of the photolyzed solution of RF in SL and ML were 27.68 and 81.10 min. The concentration of RF in solution was found 31.58% and 65.90% after 20 minutes exposure in SL and ML, respectively. In the present study, it was found that the rate of degradation of RF in aqueous solution in SL is increased upto two-fold as compare to ML because of the formation of excited species due to the intensity and nature of wavelengths absorbed by RF solutions. The present study revealed the effect of intensity of light along with wavelength emitted by SL have possessed more photodegradation of RF in aqueous solution as compared to ML.